2021
DOI: 10.1021/acs.nanolett.1c01763
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Nitrogen-Doping of Sulfur Host Nanostructures for Stable and Shuttle-Free Room-Temperature Sodium–Sulfur Batteries

Abstract: Room-temperature sodium−sulfur batteries have potential in stationary applications, but challenges such as loss of active sulfur and low electrical conductivity must be solved. Nitrogen-doped nanocarbon host cathodes have been employed in metal−sulfur batteries: polar interactions mitigate the loss of sulfur, while the conductive nanostructure addresses the low conductivity. Nevertheless, these two properties run contrary to each other as greater nitrogen-doping of nanocarbon hosts is associated with lower con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…[ 31 ] Micropores are promising reservoirs for accommodating small S molecules and retaining polysulfides. [ 32 ] Experiments by Archer and co‐workers showed that when S 8 is confined a carbon with a pore size distribution ranging from 0.6 to 1.8 nm, only insoluble short‐chain polysulfide intermediates are formed. [ 33 ] In hosts that are mesoporous, high‐order polysulfides (Na 2 S 5‐8 ) have been reported as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 31 ] Micropores are promising reservoirs for accommodating small S molecules and retaining polysulfides. [ 32 ] Experiments by Archer and co‐workers showed that when S 8 is confined a carbon with a pore size distribution ranging from 0.6 to 1.8 nm, only insoluble short‐chain polysulfide intermediates are formed. [ 33 ] In hosts that are mesoporous, high‐order polysulfides (Na 2 S 5‐8 ) have been reported as well.…”
Section: Resultsmentioning
confidence: 99%
“…The shape of the CV profiles for both electrodes agree with prior reports for a quasi‐solid‐state mechanism that includes the formation of a protective SEI layer. [ 2,8c,32,38 ] The SEI complements the role of micropores and mesopores in preventing direct contact of the electrolyte solution with the soluble sodium polysulfides intermediates. [ 39 ] After first scan, the cycle 1 cathodic peaks disappear, while two new peaks appear over the following cycles (Figure 3a and Figure S12 (Supporting Information)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–organic frameworks (MOFs), most commonly zeolitic imidazolate frameworks (ZIFs), have also been reported as suitable precursors for the microporous carbon (MPC) hosts 53–56 . ZIF‐8, synthesized from zinc nitrate and 2‐methylimidazole, is carbonized at high temperatures to obtain microporous carbon structures (Figure 4A).…”
Section: Short‐chain Sulfur Via Physical Confinementmentioning
confidence: 99%
“…The fabrication of these insoluble short-chain sulfur cathodes can be achieved via either of two broad strategies: by physically confining the sulfur in microporous carbon hosts or through covalent bonding to a composite structure . A myriad of covalently bound sulfur compounds have been investigated, including sulfurized polyacrylonitrile, sulfur- co -polymers, and more recently, organosulfur-derived thio-compounds. , Beyond these materials, there has also been emerging interest in amorphous transition metal polysulfides as sulfur cathode candidates. These amorphous metal polysulfides exhibit distinct electrochemical behavior from their crystalline counterparts, with metal–S bonds formed in the composite reportedly anchoring the sulfur species during cycling. , …”
Section: Introductionmentioning
confidence: 99%